2021
DOI: 10.26668/businessreview/2022.v7i1.277
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Malaysian university students’ intent to pursue retailing career: Applicability of theory of planned behavior

Abstract: Purpose: The retail industry offers diverse and unique career paths. However, despite the high demand for new graduates to fill managerial positions in the retail sector, their reluctance to pursue a retail career remain. This study aims to investigate the antecedents that predict retail career intention of Malaysian undergraduate business students. Theoretical framework: Using Ajzen’s (1991) Theory of Planned Behavior (TPB) as the underpinning theoretical framework, this study hypothesized that students’ inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
0
5
0
2
Order By: Relevance
“…PBC was an effective predictor of one's career intentions (Seonwoo & Jeong, 2021). In several previous career-focused research based on TPB, it was found that its generality and resiliency have been confirmed in the sense that it was found to be used to accurately predict college students' intentions to take up career paths in the areas of accounting, business management, education as well as Medical, tourism, and serving in the military (Mokhlis, Hussin, Nizam, & Noor, 2022). Although substantial quantitative research shows that the theory may be utilized as a framework for researchers to accurately determine one's career there has been currently a limited number of research studies that employ the theory of planned behavior to study business entrepreneurs' goals toward a future in commerce.…”
Section: Perceived Behavioral Control and Career Successmentioning
confidence: 82%
“…PBC was an effective predictor of one's career intentions (Seonwoo & Jeong, 2021). In several previous career-focused research based on TPB, it was found that its generality and resiliency have been confirmed in the sense that it was found to be used to accurately predict college students' intentions to take up career paths in the areas of accounting, business management, education as well as Medical, tourism, and serving in the military (Mokhlis, Hussin, Nizam, & Noor, 2022). Although substantial quantitative research shows that the theory may be utilized as a framework for researchers to accurately determine one's career there has been currently a limited number of research studies that employ the theory of planned behavior to study business entrepreneurs' goals toward a future in commerce.…”
Section: Perceived Behavioral Control and Career Successmentioning
confidence: 82%
“…Attitude includes assessment of outcomes and behavioural beliefs. The subjectivity norm consists of motivation for compliance and normative beliefs (Ajzen and Fishbein, 1975;Mokhlis et al, 2022).…”
Section: Theory Of Reasoned Actionmentioning
confidence: 99%
“…The conduct exhibited by an individual emanates from their deliberate intention influenced by a multitude of internal and external factors (Opoku, 2021). TPB was applicable as a theoreticalframework to predict intention (Mokhlis, 2021).…”
Section: Tpbmentioning
confidence: 99%